2009
DOI: 10.1111/j.1600-0501.2009.01728.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of microrough surface treatment on miniscrews used as orthodontic anchors

Abstract: There were no differences between the loaded and unloaded conditions in most groups. The RTV and BIC increased with time. In the loaded condition, the RTV of the SLA surface increased earlier, at 4 weeks, while the SL/NAOH group showed the highest RTV after 8 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 35 publications
(43 reference statements)
1
23
1
1
Order By: Relevance
“…This result was similar to that of previous studies 2526. The BV associated with unused screws was significantly higher than that associated with recycled screws, whereas there were no significant differences in BIC.…”
Section: Discussionsupporting
confidence: 91%
“…This result was similar to that of previous studies 2526. The BV associated with unused screws was significantly higher than that associated with recycled screws, whereas there were no significant differences in BIC.…”
Section: Discussionsupporting
confidence: 91%
“…26 Surface modification by sandblasting and acid etching has a beneficial effect on implant biocompatibility. 12,[27][28][29] In the present study, even with the surface visibly smooth both to the naked eye and at 503 magnification ( Figure 4), osteoblast proliferation occurred within the irregularities observed by SEM, favoring cell 12,13,18 No significant difference was observed in terms of osteoblast proliferation onto the Neodent and Morelli mini-implants; however, only for the latter was the proliferation different from that on the control, polystyrene. This result may be related to the surface similarity between the Neodent mini-implant and polystyrene (used as the control in cell-culture studies) regarding surface energy.…”
Section: Discussioncontrasting
confidence: 64%
“…Accordingly, alkali hydrothermally treated titanium implants are expected to induce excellent bone integration. In fact, several in vivo studies have reported on the benefits of alkali treatment of implant surfaces [28][29][30], and its strong effect on the chemical integration of implants with host bone. For these reasons, compared with the control group, the BIC of the alkali-treated implant showed higher values in the whole portion and the cortical bone portion.…”
Section: Discussionmentioning
confidence: 99%